2021
DOI: 10.2106/jbjs.20.01731
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Functional, and Physical Activity Outcomes 5 Years Following the Treatment Algorithm of the Delaware-Oslo ACL Cohort Study

Abstract: Background:Anterior cruciate ligament (ACL) injuries can be treated with or without ACL reconstruction (ACLR), and more high-quality studies evaluating outcomes after the different treatment courses are needed. The purpose of the present study was to describe and compare 5-year clinical, functional, and physical activity outcomes for patients who followed our decision-making and treatment algorithm and chose (1) early ACLR with preoperative and postoperative rehabilitation, (2) delayed ACLR with preoperative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
(88 reference statements)
1
13
0
Order By: Relevance
“…Follow-up was 5 years after completion of preoperative rehabilitation or ACLR. Clinical, functional, and physical activity outcomes at 2 years 11,17,18 and 5 years 43 have been reported previously.…”
Section: Data Collection and Outcome Measurementssupporting
confidence: 52%
See 2 more Smart Citations
“…Follow-up was 5 years after completion of preoperative rehabilitation or ACLR. Clinical, functional, and physical activity outcomes at 2 years 11,17,18 and 5 years 43 have been reported previously.…”
Section: Data Collection and Outcome Measurementssupporting
confidence: 52%
“…Following our decision-making and treatment algorithm, we have previously reported excellent 5-year clinical, functional, and physical activity outcomes with no statistically significant differences among the management groups. 43 To our knowledge, this is the first study to compare 5-year radiographic outcomes following a specific treatment algorithm where management was chosen based on shared decision-making. As in clinical practice, different patients choose and are recommended different managements, which increases the external validity of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, proprioception and joint position sense are not fully restored after ACL-R and this particular deficit might increase the risk of further injuries to the knee joint11 and potentially the premature development of tibiofemoral osteoarthritis 12. Although it has been reported that progressive rehabilitation alone after ACL injury may lead to good clinical and functional outcomes,13 14 preserving the native ACL with its nerve endings and vessels may also preserve proprioception 15. This may be beneficial regarding the postoperative rehabilitation, postoperative strength, return to work and sports as well as long-term joint degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…We included patients early after injury, before a 5-week rehabilitation program and shared decision-making process about treatment. Following our treatment algorithm, we have previously reported equivalent 2-year and 5-year clinical, functional, physical activity, and radiographic outcomes after progressive rehabilitation alone, early ACL reconstruction (ACLR), and delayed ACLR 13 , 33 , 34 and assessed prognostic factors for short-term outcomes. 15 , 26 , 27 , 37 …”
mentioning
confidence: 99%